Repurposing Ziyuglycoside II Against Colorectal Cancer via Orchestrating Apoptosis and Autophagy - Bai, Can; Zhang, Zhe; Zhou, Li; Zhang, Huan-Yu; Chen, Yan; Tang, Yong (Frontiers in Pharmacology, 2020)
Previous study has identified Ziyu II as a potent anti-tumor agent, but limited data on the efficacy and potential mechanism of Ziyu II in the treatment of CRC. In this study, Ziyu II exhibits antitumor activity against CRC cells both in vitro and in vivo. It demonstrated that treatment with Ziyu II induced apoptosis via accumulation of reactive oxygen species (ROS). Intriguingly, Ziyu II treatment triggered complete autophagic flux in CRC cells. Inhibition of autophagy partially reversed Ziyu II-induced growth inhibition in CRC cells, suggesting a cytotoxic role of Ziyu II-induced autophagy. Mechanistic studies showed that Ziyu II induced autophagy by inhibiting Akt/mTOR pathway, and Akt reactivation partially reduced Ziyu II-induced autophagy. Notably, Ziyu II improves the sensitivity of CRC cells to the first-line chemotherapeutic drugs 5-fluorouracil. This study provides new insights into the molecular mechanisms of Ziyu II-mediated CRC suppression involving induction of both apoptosis and autophagy, and establishes potential applications of Ziyu II for clinical CRC treatment.